HUBUNGAN ANTARA RIWAYAT MIOPIA DI KELUARGA DAN LAMA AKTIVITAS JARAK DEKAT DENGAN MIOPIA PADA MAHASISWA PSPD UNTAN ANGKATAN 2010-2012 - ., Melita Perty Arianti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background : Myopia is a refractive error with incidents between 50 % to 80,3 %at some hospitals in Indonesia. The prevalence of myopia among medicalstudents is nearly twice as high as in general population. Risk factor thatassociated with myopia is genetic or herediter and time spent in near-work.Objective : The aim to determine the association between parental myopia andtime spent in near-work with myopia in medical student faculty of medicinetanjungpura university grade 2010-2012. Method : This study was analytic observational cross sectional study. Thesamples in this study were 70 medical students faculty of Medicine TanjungpuraUniversity Grade 2010-2012, that suitable with inclusi and eksclusi criteria. Thedata was analyzed by Chi-square test with p<0,05.Result : Total subyek is 70 people, 44 (62,9%) with myopia and 26 (37,1%)without myopia.. Based on the analyze, p value has a significant association forparental myopia (p=0,010) with myopia. There were no statistically associationbetween reading book for study (p=0,961), reading book for pleasure (p value isconstant), writing (p=0,298), using laptop, handphone, and playing video games(p=0,940), watching tv (p=0,701) with myopia.Conclusion : There was significant association between parental myopia withmyopia in medical student faculty of medicine tanjungpura university grade 20102012.Therewerenosignificantassociationbetweentimespentinnear-workwithmyopiainmedicalstudentfacultyofmedicinetanjungpurauniversitygrade20102012Keywords:myopiatimespentinnear-workparentalmyopia